Structural Sterols Are Involved in Both the Initiation and Tip Growth of Root Hairs in Arabidopsis thaliana([W]) - Ovečka, Miroslav (American Society of Plant Biologists, 2010)
Structural sterols are abundant in the plasma membrane of root apex cells in Arabidopsis thaliana. They specifically accumulate in trichoblasts during the prebulging and bulge stages and show a polar accumulation in the tip during root hair elongation but are distributed evenly in mature root hairs. Thus, structural sterols may serve as a marker for root hair initiation and growth. In addition, they may predict branching events in mutants with branching root hairs. Structural sterols were detected using the sterol complexing fluorochrome filipin. Application of filipin caused a rapid, concentration-dependent decrease in tip growth. Filipin-complexed sterols accumulated in globular structures that fused to larger FM4-64–positive aggregates in the tip, so-called filipin-induced apical compartments, which were closely associated with the plasma membrane. The plasma membrane appeared malformed and the cytoarchitecture of the tip zone was affected. Trans-Golgi network/early endosomal compartments containing molecular markers, such as small Rab GTPase RabA1d and SNARE Wave line 13 (VTI12), locally accumulated in these filipin-induced apical compartments, while late endosomes, endoplasmic reticulum, mitochondria, plastids, and cytosol were excluded from them. These data suggest that the local distribution and apical accumulation of structural sterols may regulate vesicular trafficking and plasma membrane properties during both initiation and tip growth of root hairs in Arabidopsis.